3D kinematics analysis for inside leaning motions in alpine skiing - Miura, T.; Miura, M. (Science and Skiing VII, 2018)
Several studies using 3D analysis have been conducted to date (Ikegami et a!., 1987; Müller, 1994; Müller et al., 1998; Miura T. & Miura M., 2014). These studies have clarified the motion of the center of gravity of the skier and the ski system (CGss) as well as the motion of the various body segments. However, few studies have focused on the inside leaning motion (Miura T. & Miura M., 2004; Schiefermüller et al., 2005). Inside leaning motions in alpine skiing are important for turn control and the change of the turn. This study aims to clarify the skiing skill by analyzing the various body segments` motion in response to the inside leaning motion of the CGss of the skier.